Design and Explanation of a Model for Factors Affecting the Digital Marketing Environment in Global Markets - Bagheri Anilu , Saeed; Vakil Alroaia, Younos; Abdollah Heydariyeh, Seyyed (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The primary aim of this study is to design a model for factors affecting the digital marketing environment in global markets. Method: An exploratory mixed-methods research approach was employed. The qualitative part of the study is based on grounded theory. Data collection was conducted through semi-structured interviews with 19 managers and experts in digital marketing, selected using purposive and snowball sampling methods. Data analysis followed grounded theory procedures, and data were collected using MAXQDA18 software. For testing the model, research hypotheses were formulated, and a questionnaire was designed. Data were collected from 205 managers of companies active in digital marketing. Data analysis and hypothesis testing were conducted using confirmatory factor analysis and path analysis methods, employing SPSS and AMOS software. Results: A total of 242 codes and components of the model for factors affecting the digital marketing environment, comprising 41 key concepts and 20 main categories, were identified from the interviews and organized into a conceptual model based on grounded theory. The initial model was then revised and validated by experts. The quantitative phase results indicated that the path analysis model and the relationships within the model were confirmed with appropriate impact coefficients, consistent with the qualitative part. Conclusion: The paradigmatic model suggests that the primary phenomenon of the digital marketing environment is influenced by two categories: internal factors and external factors, which in turn determine the strategies of the digital marketing environment. It is crucial to recognize that this influence is not pure and occurs with the intervention of other internal and external factors. Several strategies emerged from the insights of key informants, taking into account their experiences and perceptions of the digital marketing environment in global markets. These included four main categories: business strategies, educational strategies, innovative strategies, and performance evaluation.